Extreme Vertices of the Psi-Divisible Graph of the Group Z_p^n - Kumar, Amit; Kumar, Vinod; Sehgal, Amit (IndoMS, 2026)
The Ψ-divisible graph of a finite group G, denoted by Ψ_G is a special type of simple undirected graph, in which the set of vertices contains non-trivial subgroups of G and two distinct vertices u and v are adjacent if and only if u is a proper subgroup of v such that Ψ(u)|Ψ(v) or v is a proper subgroup of u such that Ψ(v)|Ψ(u). The existence of extreme vertices in the Ψ-divisible graph of the finite cyclic group Z_p^n is described in this article.